Effect of Root Dimensions on Seed Yield and Quality of Radish (Raphanus sativus L.) cv. Pusa Himani in High Altitude Cold Arid Conditions of Ladakh - NARENDRA SINGH; ZAKWAN AHMED (Seed Research, 2026)
The present investigation was carried out to study the effect of root dimensions (root diameter and length) on seed yield and quality of radish cv. Pusa Himani during the year 2002 and 2003 in high altitude cold arid climatic condition at Field Research Laboratory, Defence Research & Development Organisation, Leh, Ladakh (J & K). The nine treatments combinations consist of three root diameters i.e. 1.5 cm, 2.5 cm and 3.5 cm and three root lengths i.e. 24 cm (full root), 16 cm and 8.0 cm (upper portion of the root) were evaluated during the experimentation. The result indicated that the root dimension had influence on plant height, number of branches, number of pods per plant and seed yield. However, survival percentage, number of seeds per pod and test weight had no significant effect during both the years. High seed yield was recorded with 3.5 cm diameter and 16 cm length of root.